Knowledge sharing dalam komunitas Global Empowerment Steps - Adya Oriza Satifa; Agus Rusmana (Faculty of Communication, Padjadjaran University, 2023)
Global Empowerment Steps is a social community with three main pillars: education, health, and the environment. The community aims to conduct social programs around Integrated Waste Disposal Sites (TPST). To maintain its three main pillars, Global Empowerment Steps always transfers knowledge among its members in making program innovations through knowledge creation. This research aims to discover knowledge sharing in knowledge creation carried out by the Global Empowerment Steps community and the key to the success of knowledge-sharing activities in the Global Empowerment Steps Community. The research method used is qualitative with a case study approach. Data collection was obtained through observation, interviews, documentation, and literature study. Informants were selected through a purposive sampling technique by selecting four community members who fit the criteria. The results of this study show that the Global Empowerment Steps community implements knowledge sharing with the method of expressing opinions through coordination meetings and informal discussions. The success factor of knowledge sharing is due to the freedom of to state opinion, a family-like organizational culture, and the blending of different background experiences. Knowledge sharing applied by Global Empowerment Steps begins with the delivery of knowledge and experience possessed by each member, documenting and disseminating knowledge, and ends with the absorption of knowledge to be practiced and disseminated into tacit knowledge again so as to produce new knowledge.